Zeis, political behavior and sewage universalization in Recife - Ferreira, Demétrius Rodrigues de Freitas (Revista Brasileira de Direito Urbanístico | RBDU, 2023)
How did the Public-Private Partnership (PPP) for sanitary sewage in Recife gain governmental agenda in 2013 with the promise of universalizing the service without serving the non-urbanized areas of the city? This article analyzed the behavior of representatives of the ZEIS areas in the discussion about the universalization of sanitary sewage in Recife. Theoretically, elements of the rational choice theory were used. Methodologically, a survey and semi-structured interviews with representatives of the areas and document analysis were used. Data obtained through interviews and documents were analyzed using the thematic content analysis technique. The results obtained suggest that the political role played by the representatives of the ZEIS favor the exclusion of the areas in the scope of intervention of the local policy of universalization of the service. In this case, two factors stand out 1) maintenance of practices of political clientelism in poor areas and 2) rational behavior of agents involved in the agenda formulation process, as determinants for the exclusion of ZEIS from the policy in question. In conclusion, it is highlighted that the articulation system between different agents with the capacity to guide priorities and investments governed by means of exchanges for benefits undermined the collective interest in the effective universalization of sewage services in the city.